Consumer preferences for purple yam (Dioscorea alata L.) powder brands implications for a product developed by the University of the Philippines Los Baños - Depositario, Dinah Pura T.; Francisco, Gelle Mae S.; Banzon, Agnes T.; Madamba, Jeanette Angeline B.; de Villa, Teodora M. (2011)
The study compares the attributes of three brands of purple yam (Dioscorea alata L.) powder, namely, Giron Powdered Purple Yam, FST Foods Purple Yam "Ubi" Powder, and Bohol's Tru Ubi Powder, and the resulting ubi halaya, a local pudding made of purple yam, made from these brands. Store checks, focus group discussions (FGDs), product and home placement tests, and a consumer survey for the local market were used as data-gathering tools. Frequency counts, mean ratings, and standard deviation were used to analyze consumer awareness, consumption behavior, and product attribute importance ratings of respondents. Kruskal-Wallis test was also employed to find out if there were significant differences in the mean ratings for all attributes across brands. The results of the study show that consumers preferred the attributes of the FST Food Purple Yam "Ubi" Powder and the halaya made using the brand. The product can thus be considered ready for commercialization by potential investors. However, it is recommended that a detailed set of product use instructions should be printed in its packaging to come up with halaya that has better taste, aroma, and consistency.
Keywords: Purple Yam; Purple yam powder